IBNU JINNĪ MENEMBUS SEKAT MAZHAB LINGUISTIK (Memadukan Aspek Logis dan Sosiologis) - Zamzam Afandi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
Abū al-Fath Usmān Ibnu Jinnī, a prolific Arabic linguist with more than forty five works, has a significant role in Arabic linguistics development. He made some efforts to cool down the tension between the two main schools of nahwu Bashra and Kufa that competed to penetrate their influence upon Arabic linguistics theories. Ibnu Jinnī, who had Motazila theological background, tried to bring the Arabic linguistic thoughts out of this conflict and took its way from hegemony of these two schools. He stood up between the two schools theories by combining the philosophical (logical) and sociological approach in discussing issues of Arabic linguistics. This article tries to examine the theory, method and approach used by Ibnu Jinnī in dealing with the linguistics issues. The article finds that Ibnu Jinnī view is that language is not a mere rational entity, but it has social dimensions. Based on this theory, Ibnu Jinnī shifted the paradigm of the Arabic linguistic issues from nah} wu based theories debate to a broader discourse and more comprehensive theories covering internal or structural aspects such as phonology, morphology, syntax as well as external aspects, notably sociology.